Spiritualitas dan Religiusitas Pasien Hipertensi - Syirli Anggriani; Kodariyah Kodariyah; Nur Insani (Jurnal Keperawatan Silampari, 2022)
This study aims to describe the picture of spirituality and religiosity in hypertensive patients at the Putri Ayu Health Center, Jambi City. This research method is quantitative research with this type of observational survey research. The results showed that the religiosity value of hypertension patients at the Putri Ayu Health Center had an average high level of 99.4%, and only 0.6% of respondents had a low level of religiosity. The spiritual value of hypertension patients at the Putri Ayu Health Center is 92%, and only 2% of respondents have a low level of religiosity. In conclusion, hypertensive patients' religiosity and spirituality values are primarily high. Keywords: Hypertension, Religiosity, Spirituality